Beyond headcount: four dimensions of Canada’s primary care access crisis and a three-level agenda for action - Najafizada, Maisam (Frontiers in Medicine, 2025)
Public debate in Canada often diagnoses a simple “shortage of family physicians,” yet system indicators point to a more complex access problem. In 2023, 17% of adults reported no regular primary care provider, only 26% obtained same/next-day appointments, and about 15% of emergency department visits were potentially primary-care-manageable—over half potentially manageable virtually. Meanwhile, average weekly physician work hours have declined by 6.9 h since the late 1980’s and the average number of patients seen per family physician fell from 1,746 (2013) to 1,353 (2021), alongside a shift away from comprehensive community practice. Drawing on comparative evidence that stronger primary care architecture is associated with better performance and that primary health care averages ∼13% of current health spending across OECD countries, this Perspective reframes Canada’s challenge across four dimensions: effective capacity (not just headcount); demand—complexity, time, and continuity; maldistribution and loss of comprehensive care; and system entry-point design. We then organize solutions in three groups: system-level (investment floors, enrollment/rostering and after-hours obligations, payment aligned to continuity and team-based comprehensiveness), organizational-level (interdisciplinary teams, task-sharing with NPs/pharmacists/PAs, operationalized continuity), and data & research (effective-FTE and continuity metrics, complexity-adjusted panel targets, rigorous evaluation of entry-point and scope reforms). Recasting the problem from headcount to capacity-and-design clarifies actionable levers for timely attachment and sustained relational continuity.